TEACHERS’ PERCEPTION TOWARD USING ENGLISH E-BOOK AT MOSLEM BASED SECONDARY SCHOOL (MADRASAH TSANAWIYAH) - Maru, Mister G.; Muhlis, Dinda C. P.; Liando, Nihta V. F. (Universitas Negeri Manado, 2023)
E-books have become a prevalent educational tool in today's learning landscape. Contrasting traditional books, the utilization of e-books displays distinct characteristics, particularly among educators who are now required to be proficient in technology-based teaching methods. This research is focused on ascertaining teachers' perceptions regarding the implications of employing e-books for English instruction at MTs Negeri 1 Bitung. The study employs a qualitative approach and involves English instructors from MTs Negeri 1 Bitung. Data collection is carried out through observation, in-depth interview and documentation. The collected data was analyzed using the Miles and Huberman theoretical framework, as follows; data reduction, data display, and drawing conclusions/verification. The findings of this study reveal that e-books offer more benefits than drawbacks. The advantages of e-books include fostering teacher creativity in developing literacy skills, innovates teaching and learning practices, lightening students’ academic load, learning flexibility, enhanced learning process efficiency, and facilitating a deeper understanding of the material. Conversely, the disadvantages encompass distractions, potential eye fatigue from screen radiation, and the necessity of a network connection.